Identifying factors influencing the corrosion rate of steel using nonparametric statistics - Nieves Mendoza, Demetrio; Gaona Tiburcio, Citlalli; Hervert Zamora, H.L.; Méndez, R.C; Castro Borges, Pedro; Borunda Terrazas, A.; Zambrano Robledo, Patricia del Carmen; Almeraya Calderón, Facundo (ESG, 2012)
Statistical techniques have made it possible to describe the behavior of certain phenomena. Nonetheless, given the difficulty in obtaining adequate data, it is common not to have random and homogeneous samples in order to conduct parametric statistical tests (which follow a known distribution). The present study reports results from the use of a non-parametric statistical test (which does not follow a known distribution) known as the Mood test of median differences which was conducted to analyze the corrosion rate of concrete beams exposed to different environmental conditions. The main objective was to statistically determine which factors accelerated the corrosion rate of the beams under study. Results showed that the tested factors (three different concrete covers: 15, 20 and 30 mm, and two water/cement ratios: 0.45 and 0.65), had statistically significant effects on the corrosion rate. Greater corrosion rates were observed for beams with covers of 15 and 20 mm, and with a water/cement ratio of 0.65. Nonetheless, we found that the corrosion rate was not statistically different between sides of the beam facing prevailing winds, and those that were sheltered from them.